(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has evolved into a global health challenge affecting multiple organ systems. Although initially recognized as a respiratory disease, accumulating clinical and experimental evidence indicates that COVID-19 is a systemic disorder with significant vascular and neurological implications. One of the most severe neurological complications associated with COVID-19 is ischemic stroke. The mechanisms underlying COVID-19-associated stroke are multifactorial and involve endothelial dysfunction, hypercoagulability, systemic inflammation, hypoxia, and genetic susceptibility. This article reviews the pathogenetic and molecular mechanisms linking SARS-CoV-2 infection with the development of ischemic stroke, emphasizing the roles of endothelial injury, cytokine-mediated inflammation, hypoxia-inducible factors, and vascular endothelial growth factor (VEGF). Understanding these mechanisms is crucial for the development of effective preventive and therapeutic strategies aimed at reducing cerebrovascular complications in patients with COVID-19.